Anisakid nematodes of the blackspot seabream, Pagellus bogaraveo, from Madeiran waters, Portugal - Costa, Graça (2022)
Two hundred and eighty-one anisakid larvae were found encapsulated in stomachs and mesenteries of 69 blackspot seabreams, Pagellus bogaraveo from Madeiran waters. Ninety-four larvae were identified as Anisakis simplex s.s., Anisakis pegreffii (Type I larvae), Anisakis simplex s.l. (Type II larvae) and Hysterothylacium sp. Prevalence of infection with anisakids increased with host length from 81.3% to a maximum of 96.3%. Mean intensity ranged from 3.5 (at length class 25 cm) to 4.8 (at length class 35 cm), with the majority of fish infected with only 1 or 2 parasites. A positive but not significant correlation was found between intensity and length (rs = 0.0419, p = 0.717). The high values of prevalence and low values of intensity may indicate that the anisakid larvae are dispersed within their hosts. No particular histopathological lesions were found associated with the presence of the nematodes, corroborated by a positive but not significant correlation that was found between intensity and condition fac tor (rs = 0.242, p = 0.035)